Musculoskeletal manifestations in diabetic patients at a tertiary center - Basavanna, Dinesha; L, Harshavardhan; Puttaswamy, Puttaswamy (International Journal of Medical Research and Review, 2016)
Introduction: Diabetes mellitus (DM) is a major public health problem worldwide. India is popularly known as a “diabetes capital of the world”. Musculoskeletal (MSK) disorders are common in diabetic patients. Objective : Incidence of diabetes and life expectancy in these patients has increased resulting in increased prevalence of musculoskeletal problems in diabetic patients. These complications may be due to metabolic or microvascular causes. This study was carried out with aim to find the prevalence and types of musculoskeletal manifestations in patients having type 2 Diabetes mellitus. Materials & Methods: A total of 300 patients with diabetes mellitus were evaluated randomly in this cross sectional study from February 2015 to March 2016 with inclusion criteria of disease duration for minimum of 1 year. Those patients who were too ill, not willing to participate and with inflammatory arthritis were excluded. Results: A total of 300 subjects were assessed for various musculoskeletal manifestations. A total of 174 subjects amounting to about 58% had the manifestation. The various complications observed in the present study were DISH (14%), Frozen Shoulder (24%), Dupuytren’s Contracture (4%), Osteoarthritis (38%), Chieroarthropathy (21%) and Flexor Tenosynovitis (8%). Conclusion: From the above observation it is clear that about 58% suffer from musculoskeletal manifestations with most common seen in knee and shoulder joint.